Literacy, the Graduation Rate, and Economic Development: How the Vaccination Approach to Literacy Instruction Impacts the Economy of Kansas and the Nation - Carolyn L. Carlson (The Advocate, 2013)
Introduction: Almost seven thousand students drop out of high school every day (Alliance for Excellent Education, 2010b). It is estimated that one in ten high schools in the United States is considered a “dropout factory” – a term given to a high school where no more than 60% of the students who begin attending the school as freshman complete their senior year (Zuckerbrod, 2007).